2011
DOI: 10.1111/j.1600-6143.2011.03478.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Infection with Epstein–Barr Virus among Seromismatch Adult Renal Transplant Recipients

Abstract: Patients who undergo Epstein-Barr virus (EBV) seromismatch (D+/R−) transplants have a higher risk for the development of post-transplant lymphoproliferative disorder (PTLD). Adult renal transplant recipients at a single institution were prospectively monitored for EBV during the first year post-transplant. Over a 2-year period, 34 patients (7.78%) were identified as being EBV D+/R− recipients. Patients who developed symptoms or had persistent viremia were pre-emptively administered rituximab. Six recipients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 15 publications
2
41
1
Order By: Relevance
“…Preemptive strategies to reduce PTLD incidence include reduction of immunosuppression, and more recently, the use of rituximab in transplant patients with persistent high-level DNAemia. Reduction in incidence of PTLD is reported in liver transplant and pediatric populations with such strategies (5)(6)(7)(37)(38)(39)(40)(41)(42). We calculated an increased risk of PTLD during follow-up for those with DNAemia at recruitment compared to those without detectable DNAemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preemptive strategies to reduce PTLD incidence include reduction of immunosuppression, and more recently, the use of rituximab in transplant patients with persistent high-level DNAemia. Reduction in incidence of PTLD is reported in liver transplant and pediatric populations with such strategies (5)(6)(7)(37)(38)(39)(40)(41)(42). We calculated an increased risk of PTLD during follow-up for those with DNAemia at recruitment compared to those without detectable DNAemia.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, preemptive reduction of immunosuppression and treatments such as rituximab may reduce the incidence of early EBV-related disease and posttransplant lymphoproliferative disease (PTLD) (5)(6)(7). In adult kidney transplant recipients, PTLD is a late event, with median time to presentation in our population of 74 months (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The utility of antiviral therapy to prevent PTLD is controversial with little evidence to support the role of acyclovir or ganciclovir in response to an elevated or rising EBV viral load without a concomitant reduction of immunosuppression. Preemptive use of rituximab in response to subclinical EBV infection began in the hematopoietic stem cell population and has recently been reported in the adult kidney transplant population [41, 42]. …”
Section: Epstein Barr Virusmentioning
confidence: 99%
“…In the only published randomized control trial, antiviral prophylaxis was not associated with a significant reduction in the risk of PTLD . Interestingly, Martin et al recently showed that treatment of primary EBV viremia with rituximab provided considerable benefit in terms of PTLD prevention. To our knowledge and based on available data, it seems that the approach of clinical, serology/quantitative EBV PCR monitoring, and subsequently preemptive reduction or cessation of immune suppression, in case of primary EBV infection, is the best method of EBV‐related PTLD prevention in EBV‐seronegative recipients.…”
Section: Discussionmentioning
confidence: 99%